'Justice and Peace Will Kiss Each Other' (Psalm 85.10b): Minjung Perspectives on Peace-building. (July 2015) - Kim, Sebastian
During the period of military-backed government (1961–1988), South Korea faced various political and economic challenges: poverty and inequality in society; human rights abuses by military governments; and confrontation with the communist North. This article examines Psalm 85: 10 in the light of the political context of South Korea and the way minjung theologians and artists understood and utilized the passage for their struggle with the governments and mega-companies. The article argues that the fight for justice for the poor and oppressed is what has brought a sustainable peace in South Korea, and that although justice seeking and peace-building should be implemented simultaneously as the Scripture implies, if one has to prioritize between the two, justice-seeking has to take precedence.